Mediation of achievement motivation on the relationship between emotional intelligence and work discipline on employee performance - Risa Pusvitasari; Moh Mukhsin; Ali Imron (Institute of Computer Science (IOCS), 2023)
The problem that is often faced by companies in achieving goals is the poor performance of employees. The purpose of this study is to analyze a model that is expected to improve employee performance by involving emotional intelligence and work discipline with achievement motivation as intervening variables in inpatient nurses at XYZ Hospital . The research method is quantitative by using a questionnaire with an interval scale of 1-10 with a sample of 115 employees from a population of 314 employees to test the five (5) predetermined hypotheses. The sructural equation model-partial least square (SEM-PLS) model was used to test the statistical significance of the path coefficient. The results of this study explain that emotional intelligence has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance, emotional intelligence has a positive and significant effect on achievement motivation, work discipline has a positive and significant effect on employee performance, and achievement motivation has a positive effect and significant to employee performance.